Modern approaches to rehabilitation phytotherapy in oncostomatology - E. V. Tsareva; A. G. Ponomareva; V. N. Tsarey (Эндодонтия Today, 2020)
A review of the literature discusses the deterioration of the hygienic state of the oral cavity and denture after the surgical, chemo-radiation and orthopedic stages of treatment for cancer of the maxillofacial region. The purpose of the study is to generalize and analyze modern research in the tield of the complex therapeutic effect of phytocomposites from medicinal plants, including anti-in^ammatory, antimicrobial, antioxidant, and oncoprotective components for use in oncological dentistry.Mouth rinses of plant origin, along with a pronounced local antimicrobial and cleansing effect, improve oral hygiene and have a phytotherapeutic effect on the body as a whole. Mouth rinses based on phytocompositions prevent the effects of chemoradiotherapy and the further development of the oncological process. The antioxidant, oncoprotective, immunomodulating and antimicrobial effects of plant ^avonoids, alkaloids and polysaccharides that systemically inhibit the process of metastasis are described.